2006
DOI: 10.1007/s00223-005-0069-9
|View full text |Cite
|
Sign up to set email alerts
|

Soy Affects Trabecular Microarchitecture and Favorably Alters Select Bone-Specific Gene Expressions in a Male Rat Model of Osteoporosis

Abstract: We have recently reported that soy isoflavones particularly when provided in the context of soy protein are capable of preventing loss of bone mineral density due to orchidectomy in F344 rats. We hypothesize, that soy isoflavones also exert beneficial effects on bone microstructural properties, in part, by enhancing bone formation. Therefore, in the present study, we examined the dose-dependent effects of soy isoflavones on femoral bone microarchitectural properties and select bone-specific gene expressions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…This suggests that daidzein can diminish cancellous bone turnover and urinary Ca excretion and maintain bone quality in gonadal hormone deficient male rats. Our observations confirm other studies describing the beneficial effects of isoflavones on the male rodent skeleton in an androgen deficiency situation [19,20,39].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This suggests that daidzein can diminish cancellous bone turnover and urinary Ca excretion and maintain bone quality in gonadal hormone deficient male rats. Our observations confirm other studies describing the beneficial effects of isoflavones on the male rodent skeleton in an androgen deficiency situation [19,20,39].…”
Section: Discussionsupporting
confidence: 94%
“…Their action relies either on the bind to the estrogen receptor (ER) or on interaction with enzymes involved in sex steroid biosynthesis and metabolism [17,18]. Several studies have demonstrated bone protective effects of isoflavones in the male skeleton [19,20]. Thus, the isoflavone, daidzein, can stimulate bone formation and inhibit bone resorption [21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…Two studies, one with ovariectomized monkeys (Jayo et al 1996) and the other with growing pigs (De Wilde et al 2001) have also found no effects of soy isoflavones on bone mineral loss, suggesting that modulation in responsiveness to soy isoflavones could be due to species and also life-stage differences. The possible role of soybean isoflavones in bone metabolism in castrated male rodents has also received attention (Ishimi et al 2002;Wu et al 2003;Khalil et al 2005;Soung et al 2006). Isoflavones seem to exert modest beneficial effects on the male skeleton in an androgen deficiency situation.…”
Section: Action Of Dietary Isoflavones On Bone In Animal Modelsmentioning
confidence: 97%
“…Another study, using human osteosarcoma osteoblasts, also reported that genistein stimulated synthesis of collagen and alkaline phosphatase, and ultimately resulted in mineralized bone modules (38). In orchidectomized rats, feeding soy isoflavones resulted in elevated mRNA levels of type I collagen, alkaline phosphatase, and osteocalcin, demonstrating that effects of genistein are not exclusive to females (39). Genistein has also been shown to act as a tyrosine kinase inhibitor, resulting in a decreased number of osteoclasts (40,41), and may modulate osteoclastogenesis by regulating mRNA expression of receptor activator of NF-B ligand (RANKL) and osteoprotegerin (42).…”
mentioning
confidence: 96%